Perception of pain in patients with chronic limb ischemia - Ponczek, Danuta; Piotrowska, Katarzyna; Felsmann, Mirosława; Humańska, Marzena (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2012)
Aim of study: The analysis and evaluation of pain in patients with chronic limb ischemia. Material and methods: The research was conducted among 59 patients with chronic limb ischemia at the Surgery Department and Clinic of Antoni Jurasz Hospital University no. 1 in Bydgoszcz. The research group comprised only adults who gave their written approval for participation in the research. The research was conducted by applying a diagnostic poll method with the use of personal data questionnaire prepared by the author, the Pain Assessment Scale by Barbara Headley and a modified Pain Assessment Form (Pain Questionnaire by McGill-Melzack.) Results : Approximately 2/3 of the subjects estimate their health as average. Despite they manage in their normal life on average, they had to change their previous duties at work. More than half of people who took part in the survey are pensioners though they are still young. The subjects showed little activity, had some problems with walking and the pain was getting worse and worse, which is alarming. Conclusions : The respondents also have some problems with doing simple housework and due to pain they lose control of their lives. More than half of respondents cannot control their pain and this is why they are taking pain killers. The correlation analysis did not show any statistically significant correlation between pain and sex, age or revascularization.